Report on Candidates' Work in the Secondary Education Certificate Examination June 1992: Mathematics - Caribbean Examinations Council (CXC, 1992)
This report contains general and specific comments on the performance of candidates in the June 1992 Caribbean Secondary Education Certificate (CSEC) general and basic proficiency examinations in Mathematics.
Keywords: CXC CSEC examinations